Properties of Biodegradable Films Based on Poly(butylene Succinate) (PBS) and Poly(butylene Adipate-co-Terephthalate) (PBAT) Blends (†) - de Matos Costa, Anna Raffaela (Polymers (Basel), 2020)
Compression molded biodegradable films based on poly(butylene succinate) (PBS) and poly(butylene adipate-co-terephthalate) (PBAT) at varying weights were prepared, and their relevant properties for packaging applications are here reported. The melt rheology of the blends was first studied, and the binary PBS/PBAT blends exhibited marked shear thinning and complex thermoreological behavior, due to the formation of a co-continuous morphology in the 50 wt% blend. The films were characterized by infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), mechanical tensile tests, scanning electron microscopy (SEM), and oxygen and water vapor permeability. PBS crystallization was inhibited in the blends with higher contents of PBAT, and FTIR and SEM analysis suggested that limited interactions occur between the two polymer phases. The films showed increasing stiffness as the PBS percentage increased; further, a sharp decrease in elongation at break was noticed for the films containing percentages of PBS greater than 25 wt%. Gas permeability decreased with increasing PBS content, indicating that the barrier properties of PBS can be tuned by blending with PBAT. The results obtained point out that the blend containing 25 wt% PBS is a good compromise between elastic modulus (135 MPa) and deformation at break (390%) values. Overall, PBS/PBAT blends represent an alternative for packaging films, as they combine biodegradability, good barrier properties and reasonable mechanical behavior.